TNF-α inhibitors in the treatment of hidradenitis suppurativa - Kevin T. Savage; Kelsey S. Flood; Martina L. Porter; Alexa B. Kimball (SAGE Publishing, 2019)
Hidradenitis suppurativa (HS) is a complex disease with a dramatic impact on the quality of life of patients that it afflicts. Despite this, there are few treatment options offering long-term relief. The exact pathophysiology of HS is unclear, although the current theory involves follicular obstruction, rupture, and subsequent inflammation leading to fistula and abscess development in intertriginous skin. Several inflammatory modulators have been implicated in the development of HS, including tumor necrosis factor (TNF)-α as well as interleukin (IL)-1β, IL-10, and IL-17. Initial evidence for the use of TNF-α inhibitors in HS stemmed from recognition that inflammatory bowel disease patients treated with these medications saw a concurrent improvement in their HS symptoms. Early case reports and case series illustrated TNF-α inhibitors' value in the treatment of HS. Later, two phase III clinical trials, PIONEER I and PIONEER II, demonstrated that adalimumab is an efficacious treatment for HS. Infliximab represents another effective HS treatment option with its main advantage being dosing flexibility. In contrast, clinical trials have failed to show evidence for application of etanercept in HS. There is limited data on other TNF-α inhibitors such as certolizumab-pegol and golimumab. This review outlines the history, dosing, response, and adverse effects of TNF-α inhibitors in the treatment of HS.